2019
DOI: 10.1002/sctm.18-0267
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Comparison of Retinal Organoid Differentiation from Human Pluripotent Stem Cells Reveals Stage Specific, Cell Line, and Methodological Differences

Abstract: A major goal in the stem cell field is to generate tissues that can be utilized as a universal tool for in vitro models of development and disease, drug development, or as a resource for patients suffering from disease or injury. Great efforts are being made to differentiate human pluripotent stem cells in vitro toward retinal tissue, which is akin to native human retina in its cytoarchitecture and function, yet the numerous existing retinal induction protocols remain variable in their efficiency and do not ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 64 publications
1
59
0
1
Order By: Relevance
“…Many teams are focusing on new methodologies to improve the quality of retinal organoids by tweaking protocols, using bioreactors, or microfluidic systems, [163,167,169,170]. Recently, Mellough et al (also with slight modification performed by Cowan et al) showed that mechanical dissociation at the embryoid body formation stage lead to improved formation of human retinal organoids [208,209]. The use of bioreactor setups, instead of static culture setups, may help solve a number of these problems as they allow for improved aeration and distribution of nutrients as well as allow for scaling up of organoid production.…”
Section: Improved Retinal Organoid Modellingmentioning
confidence: 99%
“…Many teams are focusing on new methodologies to improve the quality of retinal organoids by tweaking protocols, using bioreactors, or microfluidic systems, [163,167,169,170]. Recently, Mellough et al (also with slight modification performed by Cowan et al) showed that mechanical dissociation at the embryoid body formation stage lead to improved formation of human retinal organoids [208,209]. The use of bioreactor setups, instead of static culture setups, may help solve a number of these problems as they allow for improved aeration and distribution of nutrients as well as allow for scaling up of organoid production.…”
Section: Improved Retinal Organoid Modellingmentioning
confidence: 99%
“…Variability in size, shape, photoreceptor density, lamination determined by cell line-specific and protocol-specific differences (both derivation and maintenance) were described and documented ( Capowski et al, 2019 ; Cowan et al, 2019 ; Mellough et al, 2019 ). However, it is feasible even with current technologies to culture and maintain organoids for longer than one year, as a proof-of-principle ( Capowski et al, 2019 ).…”
Section: Lack Of Rpe Photoreceptor Interaction In Retinal Organoidsmentioning
confidence: 99%
“…Similarly to wholebrain organoids, culturing iPSC-derived EBs in predetermined conditions generates 3D optic cup-like structures together with stratified neural retinal cell subtypes and progenitors. After this seminal work, several protocols have been proposed to drive the differentiation of human iPSC toward retinal organoids (Mellough et al, 2019). Current retinal differentiation protocols can produce most relevant retinal cell types in laminated fashion with a variable efficiency in generating functional photoreceptors (Zhong et al, 2014) to retinal ganglion cells (Ohlemacher et al, 2016), and overall mature retinal tissues.…”
Section: Alzheimer's Disease In a Dish: Patient-specific Brain And Rementioning
confidence: 99%